Worldwide Meniere's disease research: A bibliometric analysis of the published literature between 2002 and 2021 - Zou, Wujun; Li, Qian; Peng, Fei; Huang, Dingqiang (Frontiers in Neurology, 2022)
Background In recent years, there has been an increasing number of publications on Meniere's disease. However, there are no bibliometric research on Meniere's disease. The purpose of this study was to find the focus and trends of Meniere's disease research through bibliometric approach. Methods Publications related to Meniere's disease in the Web of Science Core Collection (WOSCC) from 2002 to 2021 were collected. The bibliometric approach was used to estimate the searched data. Research foci of the studies were identified using VOSviewer and CiteSpace software. Results A total of 1,987 articles meet the inclusion criteria and are included in the study. In the past 20 years, the number of Meniere's disease publications is gradually increasing, especially in the past 3 years. The country with the largest contribution to Meniere's disease research is the United States, followed by Europe and Japan. High-frequency keywords included Meniere's disease, endolymphaic hydrops, vertigo, meniere-disease, inner ear, dizziness, symptoms, hearing, diagnosis, and tentamicin. The analyses of keyword burst direction indicate that evoked myogenic potential, MRI, and committee are emerging research hotspots. Conclusion This study provides an objective, systematic, and comprehensive analysis of Meniere's disease-related literature. In addition, we find a dramatic increase in studies in this field over the past 3 years. Evoked myogenic potentials and MRI may become the research hotspots of Meniere's disease in future. This study will help otolaryngologists, neurologists, and audiologists to clarify the research direction and potential hotspots of Meniere's disease and further help clinicians improve patients' prognosis.